Faktor – Faktor Yang Mempengaruhi Menstruasi Dengan Kesiapan Menghadapi Menarche Pada Siswi Di Sdit Al Qudwah G1.Mataram - Jayanti, Riski; Darmawansyah, Darmawansyah; Rossita, Taufianie (Jurnal Kesehatan Mitra Sekawan, 2025)
Menarche is the first menstruation that occurs due to a complex hormonal system process. After the five senses receive stimulation that is forwarded to the center and processed by the hypothalamus, continued with the hypophysis through the follicular system, gonadotropic follicle-stimulating hormone and luteinizing hormone are released to stimulate the ovaries. Follicle-stimulating hormone (FSH), stimulates primordial follicles which in their journey predominantly secrete estrogen hormones so that growth and development of secondary sex characteristics occur. The purpose of this research was to determine the Factors That Influence Menstruation With Readiness to Face Menarche in SDIT Al Qudwah G1. Mataram Students. The research method used is an analytical research design with a cross-sectional approach, data was collected by distributing questionnaires to 90 respondents. In SDIT Al Qudwah G1.Mataram students, the sampling technique used total sampling. The univariate results showed that respondents were aged 10 to 14 years with the largest number at the age of 14 years, namely (24.4%), Most students' knowledge about menarche was sufficient, namely (77.8%). The source of information obtained by students about menarche was (60.0%). The results of the bivariate analysis There is a correlation between knowledge and readiness to face menarche at SDIT Al Qudwah, where the P value = 0.000 P <0.05). The results of this research will add references, and prove whether or not there is knowledge, sources of information with students' readiness to face menarche at SDIT al qudwah. In addition, the results of this research can increase students' knowledge.